MODES OF SEAFLOOR GENERATION AT A MELT-POOR ULTRASLOW-SPREADING RIDGE - Cannat M.; Escartin J.; Combier V.; Sauter D.; Mendel V.; Baala M.; Ruellan E.; Okino K. (My University, 2006)
We report on extensive off-axis bathymetry, gravity, and magnetic data that provide a 26-m.y.-long record of axial tectonic and magmatic processes over a 660-km-long and melt-poor portion of the ultraslow Southwest Indian Ridge. We describe a new type of seafloor (the smooth seafloor) that forms at minimal ridge melt supply, with little or no axial volcanism. We propose possible mechanisms leading to this avolcanic or nearly avolcanic mode of spreading, in contradiction with the traditional view of mid-ocean ridges as primarily volcanic systems. We also show evidence for large-offset asymmetric normal faults and detachments at the ridge axis, with asymmetry persisting in some cases for tens of millions of years. © 2006 Geological Society of America.
Keywords: AVOLCANIC; MID-OCEAN RIDGES; TECTONIC ASYMMETRY; ULTRASLOW SPREADING